Correlation of Parasitaemia and Anemia in Mice Infected with Plasmodium berghei ANKA - Inas Hasna Azizah; Stevani Florentia Bahi; Heny Arwati; Mufassirin Mufassirin (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2023)
Malaria is an infectious disease caused by protozoa of the genus Plasmodium and transmitted through the bite of a female Anopheles mosquito. Plasmodium berghei ANKA is a species of rodent malaria parasite that is commonly used to study malaria pathology and the immune system against infections. Parasitaemia in malaria is the figure of malaria pathology due to some numbers of parasite-infected erythrocytes present in the peripheral blood. Hemoglobin (HGB) and hematocrit (HCT) levels are the parameters of anemia and some hematological changes caused by malaria infection. This study aimed to determine the correlation between parasitemia and anemia in BABL/c mice infected with Plasmodium berghei ANKA. Two uninfected and infected mice groups were compared for parasitemia, HGB, and HCT levels. Analysis statistics showed a significant difference in HGB and HCT between uninfected and infected groups. Pearson correlation analysis showed no significant correlation between parasitemia and HGB and HCT levels in infected mice. Anemia in mice infected with Plasmodium berghei ANKA can occur when parasitemia is even low; the higher parasitemia worsens the hamatological condition. Parasitemia plays a role independently in the severity of anemia. Plasmodium berghei infection in mice is useful for studying malaria anemia.